2010
DOI: 10.1007/s10479-010-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Applying the threshold accepting metaheuristic to curriculum based course timetabling

Abstract: The article presents a study of local search algorithms for timetabling problems, with the particular goal of providing a contribution to competition track 3 of the International Timetabling Competition 2007 (ITC 2007). In this track, a formulation of a curriculum based course timetabling has been published, and novel benchmark instances have been presented that allow the comparison of optimization approaches.Our heuristic local search procedure is based on the principles of Threshold Accepting, overcoming loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Recent examples of metaheuristic approaches applied to UCTPs can be found in De Causmaecker et al [16], Lü and Hao [17], Aladag et al [18], Zhang et al [19] and Geiger [20]. A hyperheuristic is a framework in which an upper-level metaheuristic selects the most appropriate heuristic out of a set of lower-level heuristics to solve a particular optimization problem (Petrovic and Burke,[8]).…”
Section: Solution Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent examples of metaheuristic approaches applied to UCTPs can be found in De Causmaecker et al [16], Lü and Hao [17], Aladag et al [18], Zhang et al [19] and Geiger [20]. A hyperheuristic is a framework in which an upper-level metaheuristic selects the most appropriate heuristic out of a set of lower-level heuristics to solve a particular optimization problem (Petrovic and Burke,[8]).…”
Section: Solution Techniquesmentioning
confidence: 99%
“…These constraints work as follows: if two consecutive lectures l and m, which are followed by series s, are planned in rooms c and d respectively, then (20) and (21) reduce to:…”
Section: ∀L ∈ Lmentioning
confidence: 99%
“…Soft constraints are used to define the objective function to be minimized. Examples of recent studies on university timetabling can be found in [1,2,4,5,6,10,12,14,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…The ITC-2007 has led to the development of many heuristic solution approaches. The five top performing approaches (finalists) of the ITC-2007 include a hybrid approach [16], a tabu search [14], a general CSP solver [2,17], a threshold accepting approach [10], and a repair-based heuristic approach [6]. These heuristic approaches produce only upper bounds to this minimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…19 A meta-heuristic is often developed in the context of a particular problem (or particular class of problem) and its performance outside of this context can therefore be variable. 20 Applications of meta-heuristics to course timetabling include: Barham and Westwood (1978);Tripathy (1980);Abramson (1991);Hertz (1991);Costa (1994);Alvarez-Valdes et al (1996);Wright (1996); Abramson et al (1999); Dimopoulou and Miliotis (2001); Mirrazavi et al (2003); Aladag et al (2009);Beligiannis et al (2009);De Causmaecker et al (2009);Moura and Scaraficci (2010);Zhang et al (2010); Al-Betar and Khader (2012); Burke et al (2012b);Geiger (2012); Pais and Amaral (2012);da Fonseca et al (2014); Lewis and Thompson (2015). 21 Applications of meta-heuristics to examinations timetabling include: Johnson (1990); Thompson and Dowsland (1998);Dimopoulou and Miliotis (2001); White et al (2004); Abdullah et al (2007); Burke et al (2010a); Özcan et al (2010); Turabieh and Abdullah (2011);Al-Betar et al (2014).…”
mentioning
confidence: 99%